PRINSIP KONSTITUSIONALISME DALAM PIAGAM MADINAH DAN RELEVANSINYA BAGI KONSTITUSI INDONESIA - El Hakim, Himas M. I. (Journal of Islamic Law Studies, 2021)
Constitutionalism is an idea that use a constitution as an instrumen for limiting state power and pro- tect human rights. Limiting state power and protect human rights is a principles of constitution that contained at every constitution. Medina’s Charter as a constitution is the first written constitution that contain it. With unique and different implementation of constitutionalism, Medina’s Charter afford good progress either state power limitation and human right protection. Syuro’ or high forum is one of the unique implementation for limiting state power and human rights protection. The result of constitutionalism of Medina’s Charter give many principle and relevance for another constitutional- ism implementation. Indonesia as a constitutional state can learn something from Medina’s Charter constitutionalism. There is formal and subsctance relevancies that was taken from Medina’s Charter constitutionalism pinciples and it can be applied at indonesia constitution.